Inheritance of purple pigmentation on vegetative parts in cowpea (Vigna unguiculata (L.) Walp.) - Ishiyaku, M.; Singh, B. (Elsevier, 2004)
Two cowpea varieties Kanannado and IAR-1696 both of which are purple pigmented on the nodal region of their main stem, base of tertiary branches, base of the stalk of the trifoliate and base of peduncle were crossed to two other varieties, IT93K-693-2 and IT87D-941-1. These two varieties are completely devoid of any pigmentation on the plant parts mentioned above. The F1, F2 and backcross populations together with the parentals were planted in the screenhouse and evaluated for pigmentation. Results showed that all the plants fell into two categories, pigmented and non-pigmented and that a pigmented plant is always pigmented all through, the nodal, bases of tertiary branches, stalk of trifoliate and peduncle. The segregation pattern in both F2 crosses fitted 13:3 ratio, P≥0.3 and P≥0.5 for the cross IT87D-941-1×Kanannado and IT93K-693-2×IAR-1696, respectively. Segregation in the backcross populations fitted 1:1 ratio in both crosses. A third cross, involving non-pigmented parents, IT93K-693-2 and IAR-48 did not show any segregation for these characters. This suggests that two genes with dominant and recessive epistasis condition pigmentation on these regions of the cowpea plant.